Visual symptoms of nutrient deficiency in physic nut - Silva, Enilson de Barros; Tanure, Luís Paulo Patente; Santos, Sheila Renata; Júnior, Paulo Sérgio de Resende (Pesquisa Agropecuaria Brasileira, 2010)
The objectives of this work were to evaluate the growth of physic nut (Jatropha curcas) and to characterize visual symptoms of macro and micronutrient deficiencies in seedlings. The seedlings were cultivated in nutritive solution required macro and micronutrients and in solutions with omission of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn or Zn, using the missing element technique. Visual deficiency symptoms and seedlings dry weight were evaluated at 90 and 120 days after treatments, respectively. The absences of macro and micronutrients in physic nut caused in nutritional deficiency visual symptoms known to other species. The deficiencies restricted the dry matter production according to the following order: Ca>Mg>K>N>P>S, for macronutrients, and Fe>Cu>Zn>Mn>B, for micronutrients.